Analisis Dampak Bullying terhadap Kecerdasan Interpersonal Siswa Kelas V di Madrasah Ibtidaiyah Sirojudin Kota Bogor - Saiful Kamal; Irvan Iswandi; Alfi Satria (Lembaga Pengembangan Kinerja Dosen, 2024)
In the field of education, students are guided to develop their potential, to hon and cultivate their interpersonal intelligence as a foundation to help them be accepted by society. Interpersonal intelligence greatly assists children forming good social relationships, which is one of the key factors to navigate daily life. Students with strong interpersonal intelligence are better able to understand and interact with others, enabling them to socialize effectively. However, the current reality shows that many children still struggle to develop interpersonal intelligence properly. For example. children often use aggressive language, mock, belittle, or tease others while playing which lead to bullying behaviors. The aim of this study is to identify the types of bullying occurred at Islamic Primary School of Sirojudin, then to assess the condition of students’ interpersonal intelligence who experiencen being bullied, and explore the relationship between interpersonal intelligence and bullying. This study refers to a qualitative method with a descriptive qualitative approach. The researcher employs interview, observation, and documentation techniques for data collection. The results of the study show that (1) the bullying occurred at the school takes the form of physical, verbal, and relational bullying; (2) bullying affects students’ interpersonal intelligence, as students who experience bullying tend to feel insecure and struggle to socialize effectively; and finally (3) bullying and students' interpersonal intelligence are correlated.